Peningkatan Aktivitas dan Hasil Belajar Siswa Kelas VI Mata Pelajaran PKN Materi Pokok Demokrasi Melalui Penerapan Model Pembelajaran Scramble Pada Siswa SD Negeri 1 Pakis Kecamatan Kradenan Tahun Pelajaran 2017/2018 - Tono, Tono (Universitas Nusantara PGRI Kediri, 2018)
Citizenship Education (Civics) is a subject that aims to form good citizens. However, students assume that Civics is a difficult subject and less interesting. Civic learning is usually centered on teachers so students feel bored and lead to low student learning activities. This causes the student learning outcomes are not optimal. Likewise, what happened to the students of class VI SD Negeri 1 Pakis Kecamatan Kradenan Lesson 2017/2018. Therefore, a classroom action research done in the school with grade VI students as the subject of his research. This study was conducted in two cycles. Data collection using interview method, observation, test, and document. The purpose of this study is to improve the activity and learning outcomes of students of class VI in learning Civics Principles of Democracy through the model of learning scramble. The results of this study indicate that the activity and learning outcomes of students in grade VI have increased through the application of learning models scramble.